The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/marc.201600815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Hydroxy-Functionalized Cyclic Olefin Copolymer and Its Block Copolymers with Semicrystalline Polyolefin Segments

Abstract: Synthesis of hydroxy-functionalized cyclic olefin copolymer (COC) is achieved with remarkably high activity (up to 5.96 × 10 g-polymer mol-Ti h ) and controlled hydroxy group in a wide range (≈17.1 mol%) by using ansa-dimethylsilylene (fluorenyl)(amido)titanium complex. The catalyst also promotes living/controlled copolymerization to afford novel diblock copolymers consisting of hydroxy-functionalized COC and semicrystalline polyolefin sequence such as polyethylene and syndiotactic polypropylene, where the gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
(17 reference statements)
0
15
0
Order By: Relevance
“…The T g of poly­(NB- co -U–OH) copolymer segment was not observed by DSC analysis due to its relatively low content in the copolymer, which could be found in our previous work . The 13 C NMR spectrum (see Supporting Information) indicated that the resonances corresponding to PNB and random PP sequences were observed together with those of the sequences of the NB/U–OH copolymer, respectively, testifying the formation of expected triblock copolymers.…”
mentioning
confidence: 99%
“…The T g of poly­(NB- co -U–OH) copolymer segment was not observed by DSC analysis due to its relatively low content in the copolymer, which could be found in our previous work . The 13 C NMR spectrum (see Supporting Information) indicated that the resonances corresponding to PNB and random PP sequences were observed together with those of the sequences of the NB/U–OH copolymer, respectively, testifying the formation of expected triblock copolymers.…”
mentioning
confidence: 99%
“…Table 1) To remove any catalyst poisons from the reactor vessel, a bomb reactor (125 mL) was charged with a solution of Me3Al (14.4 mg, 200 μmol-Al) in methylcyclohexane (17.0 g), stirred for 1 h at 100 Table 1) To remove any catalyst poisons from the reactor vessel, a bomb reactor (125 mL) was charged with a solution of Me 3 Al (14.4 mg, 200 µmol-Al) in methylcyclohexane (17.0 g), stirred for 1 h at 100 • C using a heating mantle, and the solution removed from the reactor vessel using a cannula. After completing this washing step, the reactor was charged with a solution of (CH 2 =CHC 6 H 4 CH 2 CH 2 ) 2 .0 g). This catalyst stock solution (648 mg, 4.0 µmol-Hf complex) was subsequently injected into the reactor vessel using a syringe, and the system was immediately charged with a gaseous mixture of ethylene/propylene at 20 bar pressure, which resulted in a temperature increase to~125 • C within 5 min due to the exothermic reaction, despite cooling of the reactor with a fan.…”
Section: Preparation Of (Ch2=chc6h4ch2ch2)2zn (3)mentioning
confidence: 99%
“…Following the development of a suitable strategy for the synthesis of PS-block-PO-block-PS, the CCTP reaction was performed in the presence of 3 (150 µmol) using 4 (4.0 µmol) activated with [(C 18 H 37 ) 2 MeNH] + [B(C 6 F 5 ) 4 ] − (1.0 equiv) as the catalyst. During this process, a ethylene/propylene gas mixture was fed into the system, and the polymerization temperature was maintained at 95-110 • C to prevent precipitation of the generated polymers.…”
Section: Synthesis Of Ps-block-po-block-psmentioning
confidence: 99%
See 2 more Smart Citations